Simplify the expression and write any restrictions.
![Simplify the expression and write any restrictions class=](https://us-static.z-dn.net/files/d35/50e3eec6a3782552b350e268076931a8.png)
Answer:
Numerator :
[tex]8x^2 - 10x + 3 = 8x^2 -6x -4x + 3[/tex]
[tex]= 2x(4x -3)-1(4x -3) \\= (2x-1)(4x-3)[/tex]
Denominator :
[tex]6x^2 + 3x -3 = 6x^2 +6x -3x - 3[/tex]
[tex]=6x(x+1)-3(x+1)\\=(6x-3)(x+1)\\=3(2x-1)(x+1)[/tex]
[tex]\frac{8x^2-10x+3}{6x^2+3x -3} = \frac{(2x-1)(4x-3)}{3(2x-1)(x+1)} = \frac{(4x-3)}{3(x+1)}[/tex]